Administrative Data Relationship with The Accuracy of Disease Diagnosis Codes of Inpatients in Pariaman Public Hospital - Kamal Kasra; Yudi Pradipta (Jurnal Kesehatan Masyarakat Andalas, 2022)
ABSTRACTÂ Medical records are one of the means to support the achievement of an administrative order in the context of efforts to improve health services in hospitals. An important thing that must be considered by medical record personnel is the accuracy in providing diagnosis and procedure codes. The research problem is the accuracy of the coding of the Diagnosis & Procedure on the medical records of inpatients at the Pariaman Regional General Hospital. The research objective was to describe the general characteristics and accuracy of disease coding based on diagnosis and service procedures as well as the impact of the accuracy of disease coding with inpatient disease diagnosis on the quality of service at the Pariaman Regional General Hospital. The research method is mixed methods. A quantitative approach to the patient's medical record file and a qualitative approach were obtained through FGDs with medical record management officers. The results showed that the accuracy of the main Diagnosis coding has shown results that exceed 80% of all medical records of patients selected as the study sample. However, the accuracy of the secondary diagnosis code is only 50%. Procedure code acceleration is still very low at only 15.4%, and secondary procedure only at 1.8%. The conclusion of the study, the accuracy of the diagnosis code and procedures is closely related to the quality of service. Inaccuracy of diagnosis codes as well as procedures will affect patient satisfaction, especially in payments that are not in accordance with the services they receive. Â Keywords : Encoding, Diagnosis, Procedure, Medical records